CLINICAL AND PARACLINICAL INDICATORS IN THE ESTABLISHMENT OF AN ORAL DIAGNOSIS WITH HIGH PREDICTABILITY - Dragoş Frăţilă; Mihaela Monica Scutariu; Norina Forna (Romanian Society of Oral Rehabilitation, 2014)
Predictability is a key condition for the development of the health system. The success of a dental treatment is conditioned by an accurate diagnosis, in conjunction with an appropriate treatment plan. A diagnosis can be established when one or more diagnostic signs are present. The initial diagnosis is further characterized using one or two risk factors. For every patient that will be treated, it is made a dental folder that contains the survey, and a series of paraclinical examinations. At any time we can detect the existence of some elements of predictability of the general disease with impact at the level of the oral cavity. Due to the wide spread of the illness and of the difficulties of therapeutic order in advanced forms of the disease. In recent decades there have been made special efforts in the direction of their diagnosis in the early stages. There are not always forms of chronic or acute, appeared in the oral cavity, which can be considered in its own right, but may be correlated with a general known pathology or not known to the patient.